Differential GPS performance: ground versus geostationary satellite - Saab, Samer S. (2000)
When GPS measurements are made by two users within the same GPS satellite transmission sight, the associated errors are mainly similar. Consequently, knowing the exact location of the receiver with respect to GPS satellites within view allows the measurements errors to be estimated. Thus, these error estimates may be extracted by other nearby GPS users if relayed properly. This correction scheme is the idea behind Differential GPS (DGPS). There are two basic differentiating techniques: one employs a ground station and the other uses a geostationary satellite as reference benchmarks. The purpose of this paper is to compare the performance of the two differentiation techniques in Lebanon. The experiments presented in this paper investigate the nature and magnitude of the errors in the upward direction. These errors are also compared with errors in the level plane.